The Use of the Self-Selected Rest Interval Method Is as Effective for Optimizing Postactivation Performance Enhancement in Elite Athletes as Employing the Best Fixed Rest Interval - Fontanetti, Gabriel [UNESP]; Barreto, Renan V. [UNESP]; Junior, Rubens C. [UNESP]; Marangoni, Victor [UNESP]; Denadai, Benedito S. [UNESP]; Greco, Camila C. [UNESP]; Lima, Leonardo C.R. [UNESP] (Wolters Kluwer, 2025)
This study investigated whether the adoption of a self-selected recovery interval (SSI) is more effective than the use of a fixed recovery interval (FRI) to elicit postactivation performance enhancement (PAPE). Ten male professional volleyball athletes (20.6 ± 1.5 years; 92.8 ± 4.9 kg; 195 ± 8 cm) participated in 3 experimental sessions, in random order, following familiarization with countermovement jump (CMJ) exercises and determination of the load for 5-repetition maximum (5RM: 146 ± 27 kg) squat exercise. The 3 experimental sessions consisted of (a) control session (CON), with measurement of CMJ height 4 minutes before and 2, 4, 6, 8, and 10 minutes after subjects rested while sitting in a chair without performing any preactivation (PA) protocol; (b) session with FRI, with measurement of CMJ height 2, 4, 6, 8, and 10 minutes after performing a PA exercise consisting of 5 squats with 5RM load; and (c) session with SSI, with evaluation of CMJ height once after performing the PA adopting a SSI based on a readiness scale. No significant differences were found between CMJ height in the CON session. Countermovement jump height was higher (p < 0.05) than the baseline measurement at minutes 4, 6, and 8 post-PA in the FRI session, for the best CMJ performance during the FRI session, and after the PA in the SSI session. No significant differences were found between the heights of the best CMJ in the FRI session (49.2 ± 6.8 cm) and post-PA in the SSI session (49.6 ± 6.6 cm). Therefore, adopting FRI and SSI is equally effective in eliciting PAPE in elite athletes. Despite being as effective as adopting FRI to elicit PAPE, SSI is more intuitive and easily applicable in contexts where PAPE can be implemented.
Keywords: countermovement jump; jump performance; postactivation potentiation; power; recovery; self-regulation